Polymer recycling - Wolfson S A (Polymer Science Series C, 2000)
Modern methods employed for recycling of used polymeric materials such as plastics, vulcanised rubbers (including tyres), and various polymer-containing composites are reviewed and the general trends in the development of these processes and their place in the technology, economics and ecology of the 21st century are analysed. Special attention is paid to principally new approaches to the problem of polymer recycling. High possibilities offered by the polymer pulverisation method based on the high-temperature shear extrusion process, known as the solid state shear pulvarisation technology, are demonstrated for recycling of used tyres, various polymer blends and polymer-based composites. Some factors affecting public opinion concerning utilisation of wastes are considered in relationship with the general problem of balance between the production, consumption and utilisation of used polymeric materials.
Source Year: 2001
Keywords: Polymer blends; Polymer recycling; Polymeric materials